A Single Dras‐Kohistan‐Ladakh Arc Revealed by Volcaniclastic Records. (10th March 2022) - Andjić, Goran; Zhou, Renjie; Jonell, Tara N.; Aitchison, Jonathan C.
Abstract: Tectonic interpretations of arc remnants in the Himalayan orogen remain uncertain, despite their important implications for the overall convergence history between India and Eurasia. Provenance results from deep‐water volcaniclastic rocks of the Indus Suture Zone in Ladakh provide new constraints on the Mesozoic tectonic evolution of the Dras and Kohistan‐Ladakh arcs. Detrital zircon (DZ) U‐Pb ages and whole‐rock geochemistry of the fault‐bounded Upper Cretaceous Nindam and Paleocene Jurutze formations present age patterns and compositions that are consistent with those of the Dras and Kohistan‐Ladakh arcs, respectively. The combination of DZs of the Nindam and Jurutze formations with the igneous zircons of the Dras and Kohistan‐Ladakh arcs shows similar age distributions that support a Late Jurassic to Paleocene tectonic connection between all these units. We argue that the secular trends in geochemical composition of DZs and volcaniclastic material are consistent with the magmatic evolution of one convergent margin, which shifted from a primitive to a mature stage during the Late Cretaceous. The recognition of a single Dras‐Kohistan‐Ladakh arc sets the stage for reevaluating competing scenarios of the Mesozoic evolution of the India–Eurasia convergent system. We find that the most likely scenario is that of a Jurassic arc formed above a south‐dipping intraoceanic subduction zone and accreted to Eurasia during the Early Cretaceous, after which it evolved above a north‐dipping subduction zone. Plain Language Summary: The Himalayan orogen is the result of the collision between India and Eurasia and the closure of the intervening Neotethys Ocean. The suture zone between India and Eurasia hosts an incomplete and complex archive of the paleogeography that once existed between them prior to continent‐continent collision. Investigating suture zone rocks may therefore provide valuable information on the building blocks of the orogen and the overall history of the India‐Eurasia convergent system. Disparate remnants exposed in the Indus Suture Zone (Western Himalaya) suggest that volcanic arcs and sedimentary basins were formed above intraoceanic subduction zones, but there is no consensus on their original paleogeography. We discuss new and existing geological data from volcaniclastic rocks related to the Dras and Kohistan‐Ladakh arcs. Our data support the existence of a single Dras‐Kohistan‐Ladakh arc during the Mesozoic and provide additional insights into the complexity of the pre‐collisional convergence between India and Eurasia. Key Points: Dissimilar ages and compositions of volcaniclastic units in the Indus Suture Zone reveal arc evolution from primitive to mature stages Detrital zircon U‐Pb ages and geochemistry, and whole‐rock geochemistry support a common origin of the Dras and Kohistan‐Ladakh arcs The recognition of a single Dras‐Kohistan‐Ladakh arc represents a key constraint in models of India‐Eurasia convergence